Pengaruh Citra Merek terhadap Minat Beli Ulang melalui Keterlibatan Pelanggan pada Produk Teh Gelas - Fadhil Muhammad Slapa; Haryadi Triwahyu Putra (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2025)
The dynamics of the bottled tea beverage industry in Bandung has become very competitive and firms are forced to not only capture the initial purchase but also to maintain consumer loyalty, which is through repeat purchases. This research aims to examine the influence of brand image on repurchase intention, with customer involvement acting as a mediating variable, in the context of Teh Gelas bottled products in Bandung City. The decline in Teh Gelas’s Top Brand Index over the past three years serves as the research background, indicating a reduced level of repurchase intention, particularly among Generation Z consumers. This research used purposive sampling method with quantitative approach, 120 respondents were selected aged 17-27 years and living in Bandung City. The data were analysed as a multiple linear regression model with the Sobel test determining the presence of the mediation effect. The findings reveal that brand image exerts a positive and significant impact on both customer engagement and repurchase intention. However, customer engagement shows a significant negative effect on repurchase intention. Moreover, the mediating role of customer engagement in the relationship between brand image and repurchase intention was found to be insignificant. These results underscore the importance for companies to strengthen their brand image and design effective engagement strategies to enhance customer loyalty and drive repurchase behavior.